Factors associated with severe postpartum haemorrhage: systematic review using Bradford Hill’s causality framework - Tatiana Stachetti; Michel Spodenkiewicz; Arnaud Winer; Malik Boukerrou; Julie Jesson; Patrick Gérardin (Journal of Global Health Reports)
# Background